Influence Of Rearing System On The Production Performance Of Commercial Layers (Applied Biological Research, 2012)
A study was conducted by collecting data from 60 commercial layer  farms (15 farms in deep litter system, 25 farms in cage system and 20  farms in cages on elevated platform system) to assess the influence of  housing system on production performance of commercial layers. The  overall hen day egg production (21-72 weeks) was significantly higher in  conventional cage system (78.85±0.70) and cages on elevated platform system (80.15±1.19) comparedtodeep litter systemof rearing(72.41± 0.51).  The system of rearing had significant influence on feed efficiency for each  production period as well as full production period. The values were 1.66 ± 0.02, 1.63 ± 0.02 and 1.86 ± 0.02 in conventional cages, cages on elevated  platform and deep litter system of rearing, respectively. The feed  consumption was significantly higher in deep litter system in comparison to other two rearing systems. The livability was significantly lower in  deep litter system of rearing (85.94 ± 0.36) than conventional cage system  (89.32 ± 0.90) and cages on elevated platform system (89.39 ± 1.08).
Keywords: Egg production; feed efficiency; layer; livability; rearing system